Single minimal conjunctival incision for rectus muscles: a pilot feasibility study - Jaime Tejedor; Francisco J. Gutiérrez-Carmona (Therapeutic Advances in Ophthalmology, 2025)
Background: Small conjunctival incision size is desirable in strabismus surgery under topical anesthesia. Objective: To study the feasibility and tolerability of a small bulbar conjunctival incision (SB). Design: Non-randomized feasibility pilot study. Methods: After applying a 5-0 PGA (polyglycolic acid) traction suture, we did a 3–4 mm single conjunctival incision posterior and parallel to the rectus muscle insertion. A hang-back recession was done (6-0 PGA suture), and the conjunctiva closed (8-0 PGA suture). The outcome measures were feasibility, tolerability, and motor result. Results: Twenty-five patients were included. The median pain scale score was 3/10, and the satisfaction Net Promoter Score was 72. Mean duration of a recession was 12 min (range: 9–14 min). Mean duration of inflammatory signs and hemorrhage were 2.2 days (95% CI, 1.4–2.9), and 8.5 days (95% CI, 7.1–9.9), respectively. Distance deviation at 2 months was 3.1 Prism Diopters (95% CI, 1.5–4.5). Conclusion: SB is feasible and well tolerated for extraocular rectus muscle surgery.